Hayward Tyler to acquire UK engineering firm Peter Brotherhood. Issue 10 (October 2015) - Unknown
Abstract : Hayward Tyler Group plc is buying UK engineering company Peter Brotherhood from Dresser-Rand Co Ltd, a Siemens-owned business, for US15 million.